Perencanaan dan Penjadwalan Pariwisata dengan Konsep Jejaring Sosial - Meiliana, Meiliana; Nugraha, Krishna; Liemunandar, Kevin (Bina Nusantara University, 2014)
Most of tourist will choose new unvisited tourism spot as their new tourism destination. However, limited information of the new tourism destination often becomes a barrier to plan and schedule their tourism activity. The purpose of this research is to create an application called IndoLista, to provide complete tourism spot information, create tourism planning and schedule with social media concept. The social media concept will facilitate communication and interaction between user to get updated information in effective way. Eachuser will be able to organize their tourism planning with application's feature provided, completed by detail information of tourism spot. Research methodology is divided into two parts; analysis method by book andjournals study literature, analyze similar application, user data collection with quisioner and and design method with UML tools. Quisioner evaluation conclude society opinion that the application as research result, give asolution to user in the interest of planning and schedulling online tourism trip by providing complete information of tourism spot and facilitating interaction and communication between user via social media concept.